Adhesion of patients with diabetes mellitus to pharmacological and non-pharmacological treatment: an integrative literature review (Research, Society and Development, 2022)
The present study aimed to identify in the literature how the adherence to the treatment of people with diabetes mellitus happens, considering its weaknesses and potential. This study, if by an integrative literature review of descriptive character, with a qualitative approach. To systematize the search for the collection of studies and sampling of the literature, the following databases were used: BDENF, LILACS, MEDLINE, SCIELO and PubMed, using the following descriptors: Diabetes mellitus, diabetes complications and quality of life. Articles published in full from 2016 to 2021 were included in the study. Regarding the results, there was a reduced reduction in serum glucose in relation to those patients who used the correct therapies, whether aimed at the rational use of hypoglycemic medications or through adherence to physical activity and the introduction of a correct diet, a situation that managed to reduce the appearance of serious complications and hospitalizations. As well as the use of pharmacological therapies and the risk of drug interactions arising from incorrect treatment, which often permeates the deficiency in medical guidance or lack of educational instruction. Thus, there is a need for adherence by these people with diabetes, both for a healthy quality of life, through the introduction of activity and correct nutrition, as well as through physical guidance booklets that served as a resource for the prevention of complications related to uncontrolled blood glucose levels.